Η ΣΥΓΚΡΟΤΗΣΗ ΤΗΣ ΜΝΗΜΗΣ ΣΤΗΝ ΠΡΟΤΕΣΤΑΝΤΙΚΗ ΠΡΟΠΑΓΑΝΔΑ ΣΤΗ ΔΙΑΡΚΕΙΑ ΤΩΝ ΓΑΛΛΙΚΩΝ ΘΡΗΣΚΕΥΤΙΚΩΝ ΠΟΛΕΜΩΝ ΤΟΥ 16ου ΑΙΩΝΑ - ΓΑΓΑΝΑΚΗΣ, ΚΩΣΤΑΣ (Μνήμων, 1998)
Costas Gaganakis, The construction of memory in Protestant propagandaduring the French Religious Wars Subject of this article is the construction of collective, group memory,by French Protestant propagandists, such as Jean Crespin, during the troubled years of the French religious wars. The invention of a heroicpast, as constitutive element of Huguenot identity, not only served thepurposes of an imagined community, but equally sought to come toterms with the pressing political situation of the day. Huguenot polemicists,like François Hotman, also attempted to reconstruct Frenchnanional memory (and identity), by referring to an invented nationalpast, in order to justify their open rebellion against the French monarchy,especially following the events of August 1572.The insistence on the history of the martyrs, on the biblical identityof the Huguenots, served to consolidate inner bonds and to cultivatea sense of heroic perseverance for the persecuted minority. Huguenotcollective memory not only served to mould collective religious identity,but it also helped to promote a distinct political identity, that of afully loyal and wrongly persecuted, patriotic minority.